Kepemimpinan Kiyai Sebagai Pemimpin Pendidikan Di Pondok Pesantren Nurulhuda Pakandangan Barat Sumenep - Abdul Azis (El-Idare, 2017)
This study aims to reveal the role of Kiyai as a leader of education at Pondok Pesantren Nurulhuda Pakandangan Sumenep. The type of research used in this study is qualitative research. The result of research shows that kiyai as education leader has three role that is first class as manager, management of boarding school is directed to the achievement of pesantren goal. Decision making is conducted in the annual meeting forum as well as quarterly meetings as a form of formative evaluation of activities that have been implemented. second, the role of leader, leadership style used is participative leadership by involving all components of boarding school consisting of board, council asatidz, and representation santri.dan third role as curriculum developer, curriculum used in Pondok Pesantren Nurulhuda combine two curriculum that is curriculum which is the provision of government and self-developed curriculum. Using Arabic and English as the language of instruction in every lesson is also the everyday language of santri. The yellow book is also taught in class with the aim of recognition, understanding, practice, and motivation.